2019
DOI: 10.1111/jcmm.14262
|View full text |Cite
|
Sign up to set email alerts
|

A functional interaction between Hippo‐YAP signalling and SREBPs mediates hepatic steatosis in diabetic mice

Abstract: The Hippo pathway is an evolutionarily conserved regulator of organ size and tumorigenesis that negatively regulates cell growth and survival. Whether the Hippo pathway regulates cell metabolism is unknown. Here, we report that in the nucleus of hepatocytes, Yes‐associated protein(YAP)—the terminal effector of the Hippo pathway—directly interacts with sterol regulatory element binding proteins (SREBP‐1c and SREBP‐2) on the promoters of the fatty acid synthase (FAS) and 30‐hydroxylmethyl glutaryl coenzyme A red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 52 publications
(80 reference statements)
1
42
1
Order By: Relevance
“…YAP/TAZ has been reported to interact with mature SREBPs within the nucleus leading to enhanced transcriptional activities and increased expression of downstream targets, such as HMGCR and the fatty acids synthase (FAS). Activation of the Hippo signaling pathway was found to reduce hepatic steatosis in diabetic mice 126 . YAP also appears to participate in regulating FAO, and thus in helping cancer cells undergoing metastasis via the tumor‐draining lymph nodes (LNs) to survive within the LN microenvironment 127 .…”
Section: Molecular Mechanisms Of Lipid Metabolic Reprogrammingmentioning
confidence: 99%
“…YAP/TAZ has been reported to interact with mature SREBPs within the nucleus leading to enhanced transcriptional activities and increased expression of downstream targets, such as HMGCR and the fatty acids synthase (FAS). Activation of the Hippo signaling pathway was found to reduce hepatic steatosis in diabetic mice 126 . YAP also appears to participate in regulating FAO, and thus in helping cancer cells undergoing metastasis via the tumor‐draining lymph nodes (LNs) to survive within the LN microenvironment 127 .…”
Section: Molecular Mechanisms Of Lipid Metabolic Reprogrammingmentioning
confidence: 99%
“…Previous studies have shown that YAP/TAZ promotes fatty acid and triglyceride synthesis by upregulating FAS ( 11 , 96 ), ACL ( 11 ), ACC ( 11 , 96 ), and SCD-1 ( 11 , 96 ) through upregulated SREBP1. In addition, YAP/TAZ reportedly upregulated 30-hydroxymethyl glutaryl coenzyme A reductase ( 96 ) in cultured C57BL/6 mouse hepatocytes, by upregulating SREBP2, which in turn increased cellular cholesterol synthesis. In vitro HCC experiments revealed that YAP/TAZ promoted cancer cell proliferation by increasing lipid formation ( 11 ).…”
Section: Ecm Stiffness and Lipid Metabolismmentioning
confidence: 99%
“…The sterol regulatory element-binding proteins (SREBPs) are transcription factors that control the expression of enzymes involved in fatty acid and cholesterol biosynthesis (146). It has been reported that YAP interacts with the nuclear forms of SREBP1 and SREBP2 and enhances their transcriptional activities toward fatty acids synthase (FAS) and 30-hydroxylmethyl glutaryl coenzyme A reductase (HMGCR) (147). Also, the study has shown that the activation of LATS1 or inhibition of YAP reduced hepatic steatosis and hyperlipidaemia in diet-induced diabetic mice (147).…”
Section: The Role Of Yap/taz In Lipid Metabolismmentioning
confidence: 99%